Beta-thalassemia genes in French-Canadians: haplotype and mutation analysis of Portneuf chromosomes. - Kaplan, F (1990)
beta-Thalassemia minor occurs at approximately 1% frequency in French-Canadians--in families residing in Portneuf County (population approximately 40,000) of Quebec province. We found eight different RFLP haplotypes at the beta-globin gene cluster in 37 normal persons and in 12 beta-thalassemia heterozygotes from six families. beta-Thalassemia genes in these families associated with two haplotypes only: Mediterranean I and Mediterranean II. There were two different beta-thalassemia mutations segregating in the Portneuf population: an RNA processing mutation (beta(+)IVS-1,nt110) on haplotype I (five families) and a point mutation leading to chain termination (beta(0) nonsense codon 39) on haplotype II (one family). The distribution of 5' haplotypes on normal beta A Portneuf chromosomes compared with other European populations was most similar to that in British subjects (data for French subjects have not yet been reported). Genealogical reconstructions traced the ancestry of carrier couples to settlers emigrating from several different regions of France to New France in the 17th century. These findings indicate genetic diversity of a greater degree among French-Canadians than recognized heretofore.